Signature of the πNN configurations in coherent πphotoproduction on the deuteron; The European Physical Journal A - Hadrons and Nuclei; Vol. 26, iss. 2 - Fiks (Fix) A. I. Alexander Ivanovich (2005, 2005)
Title screen